PENGARUH KECERDASAN EMOSIONAL DAN STRES KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (STUDI PADA KANTOR KESYAHBANDARAN UTAMA BELAWAN) - Yan rizal (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
The formulation of problem in this research there is influence  of emotional intelligence on  motivation. There is influence  of job stress on  motivation. There is  emotional intelligence on employees performance. There is  job stress on employees performance. There is   motivation on employees performance. The purpose of this research is for know influence and analize of   emotional intelligence on  motivation. For know influence and analize   of job stress on  motivation. For know influence and analize of  emotional intelligence on employees performance. For know influence and analize of job stress on employees performance. For know influence and analize of    motivation on employees performance. The sample in this research is 60 employees, with data analysis technique used is descriptive analysis and multiple linear regression analysis. The research result  is emotional intelligence variable influence positive and don’t significant on  motivation. Job stress variable influence negative and don’t significant on  motivation. Emotional intelligence variable influence positive and  significant on employees performance. Job stress variable influence positive and  significant on employees performance.  Motivation  variable influence negative and  don’t significant on employees performance. Emotional intelligence and job stress variable influence positive and  significant on employees performance with  motivation as moderasi variable